2015
DOI: 10.25100/cm.v46i2.1652
|View full text |Cite
|
Sign up to set email alerts
|

Variaciones de la relación anatómica de la arteria carótida común y la vena yugular interna. Estudio ecográfico

Abstract: Introduction: The internal jugular vein locates anterior or anterolateral to the common carotid artery in two-thirds of the subjects studied by ultrasound when the head is in a rotated position. Aim: To identify variables associated with the anterior location of the internal jugular vein. Methods: Ultrasound examinations were performed with the patients in the supine position, with the head rotated to the opposite side. The proximal third of the neck was visualized transversely with a 7.5-mHz transducer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Current guidelines for central venous access encourage the use of ultrasound guidance but do not consider the variability of the positions and dimensions of the vessels (American Society of Anesthesiologists, 2020). Previous research has suggested at least five variations in positioning between the IJV and the CCA, with the IJV anterior overlapping the CCA in only 35.8% of the sample (Umaña Perea et al, 2015). This study has further investigated geometrical measures of the vessels and found that the depth of the right IJV more closely correlates with the individual's BMI than the depth of the left IJV (Table 1).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Current guidelines for central venous access encourage the use of ultrasound guidance but do not consider the variability of the positions and dimensions of the vessels (American Society of Anesthesiologists, 2020). Previous research has suggested at least five variations in positioning between the IJV and the CCA, with the IJV anterior overlapping the CCA in only 35.8% of the sample (Umaña Perea et al, 2015). This study has further investigated geometrical measures of the vessels and found that the depth of the right IJV more closely correlates with the individual's BMI than the depth of the left IJV (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in adult populations attempted to characterize the fenestrations in the IJV (Abakay et al, 2019; Mumtaz & Singh, 2019; Pegot et al, 2015) and positional variations of the IJV (Lorchirachoonkull et al, 2012; Umaña Perea et al, 2015); geometric parameters and modeling have mainly been studied in pediatric populations (Lee et al, 2017). More specifically, there has been an effort to determine the optimal depth of the IJV for central line placement, both in pediatric and adult populations (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…IJV may differ due to anatomical differences, the movement of head, or the position of probe. 29 Second, IJV wall is thinner than CCA. The probe is slightly under pressure and IJV is prone to deformation, thus making the diameter and cross-sectional area to become smaller or disappear.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in ROI selection and individual anatomy differences can also cause inconsistent correlation results. Umaña et al found that about 41.1% of the observations show that the internal jugular vein was significantly overlapped with a carotid artery on the left side of the neck 32,33 . Furthermore, the lateral position of the internal jugular vein was approximately 26.5% on the left side of the neck 32,33 .…”
Section: Discussionmentioning
confidence: 99%